Bibliometric mapping of non-invasive brain stimulation techniques (NIBS) for fluent speech production - Medeiros, Wesley; Barros, Tayná; Caixeta, Fabio V. (Frontiers in Human Neuroscience, 2023)
Introduction Language production is a finely regulated process, with many aspects which still elude comprehension. From a motor perspective, speech involves over a hundred different muscles functioning in coordination. As science and technology evolve, new approaches are used to study speech production and treat its disorders, and there is growing interest in the use of non-invasive modulation by means of transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS). Methods Here we analyzed data obtained from Scopus (Elsevier) using VOSViewer to provide an overview of bibliographic mapping of citation, co-occurrence of keywords, co-citation and bibliographic coupling of non-invasive brain stimulation (NIBS) use in speech research. Results In total, 253 documents were found, being 55% from only three countries (USA, Germany and Italy), with emerging economies such as Brazil and China becoming relevant in this topic recently. Most documents were published in this last decade, with 2022 being the most productive yet, showing brain stimulation has untapped potential for the speech research field. Discussion Keyword analysis indicates a move away from basic research on the motor control in healthy speech, toward clinical applications such as stuttering and aphasia treatment. We also observe a recent trend in cerebellar modulation for clinical treatment. Finally, we discuss how NIBS have established over the years and gained prominence as tools in speech therapy and research, and highlight potential methodological possibilities for future research.